A Study on the Knowledge Implementation Strategy and its influence on the Knowledge Sharing Attitude among Knowledge Workers and Individual Job Performance - Lim, Tong-Ming; ., Angela Lee (Journal of Economics and Behavioral Studies, 2013)
Knowledge is asset that empowers individual and organizations to stay competitive in a borderless business world. For organizations that successfully deploy knowledge sharing and reuse, they have claimed to have observed job performance improvement. Even though the success or failure of KM implementation have been aggressively investigated by researchers, nevertheless, besides factors such as culture, business strategy, size, capacity and needs of organizations, KM strategy may vary depending on the organizations’ eco-system. Hence, there is a need to investigate organizations operate in Malaysian to understand influences of KM strategy and its influence to knowledge sharing atttitude among knowledge workers in the organizations. And the effect of KM strategy and knowledge sharing atttitude on individual job performance. The research subjects are IT related companies in Malaysia that practise knowledge sharing. MSC status companies will be invited to participate. Questionnaire will be sent to these companies to solicit responses. Structural Equation Modelling (SEM) will be adopted as analysis technique to analyze the responses from research subjects that take part. In this research, a selected group of companies in Kuala Lumpur/Selangor/Klang Valley will be interviewed to collect their views for qualitative analysis. Campbell Job Performance Theory will be used in the research to evaluate performance of knowledge workers in organizations. Questionnaire survey will be circulated to knowledge workers to collect their responses. The outcomes of the research provides a better understanding of the relationships between KM implementation strategy, knowledge sharing attitude, and individual job performance of knowledge workers.